Measuring Brand Recall in Print Media Advertising:A Study of Selected Brands of Personal Care Industry - Faldu, Rajesh (Indian Journal of Marketing, 2009)
Evaluation of effectiveness of advertisements is always a major task before the advertiser owing to changes in the market environment. Making the advertisements and placing it in appropriate media is of great importance to realize the ultimate objective. Brand Recall plays a very important role in advertising for boosting more sales. This article is based on the study of evaluation of the print media advertisements of selected brands of Personal care industry for measuring advertising effectiveness in print media. Data analysis has been carried out at 5% significance level of the selected brands with respect to personal variables. It has been found that there is significant difference between the recalling ability of the respondents. Recommendations are given in the form of suggested model for the enhancement of ad effectiveness in print media.